Estimating leopard density in a coastal protected area of the Western Cape, South Africa - Hargey, Ayesha (Department of Biological Sciences, 2023)
Leopards (Panthera pardus), like many other large carnivores, are facing increasing threats including habitat degradation, illegal hunting, and persecution for perceived or actual livestock depredation. Protected areas remain the cornerstone of conservation efforts throughout the world but they are not a panacea and recent studies have shown declining populations within many protected areas of South Africa. Efforts to improve leopard conservation are hampered by a lack of reliable and repeated estimates of population size across their distribution, which limits an understanding of population dynamics and the potential drivers of declines. Monitoring efforts that produce density estimates are invariably the most informative for reserve managers who work with endangered species and are responsible for regional conservation planning – especially in cases where both predator and prey are of vulnerable populations. A small coastal area within the De Hoop Nature Reserve has been fenced off from the reserve with the goal of establishing a mainland breeding colony for the endangered African penguin (Spheniscus demersus). The fence is designed to reduce the threats posed by terrestrial predators, particularly leopard and caracal (Caracal caracal). Both feline species engage in supernumerary killings of penguins due to their poor predator response and are thus of special relevance to reserve managers and NGOs committed to their conservation. In this study, I conducted a camera trap survey in the De Hoop Nature Reserve, along the south coast of the Western Cape with the primary objective of estimating the density of leopards and the secondary goal of understanding the distribution, abundance, and activity patterns of leopard and caracal relative to the proposed penguin colony. I deployed 40 paired camera trap stations over 2457 trap nights and captured 312 independent images of the target taxa. A sample-based species accumulation curve revealed a clear asymptote indicating adequate sampling effort and a total of 24 medium and large mammal species. Both leopard and caracal had high relative abundance indices at camera stations close to the designated penguin colony. I recorded 111 independent images of leopards, of which six males and one female could be reliably identified. I derived a density estimate of 0.18 ± 0.07 individuals per 100km2 which is lower than estimates for protected areas in the eastern and northern regions of South Africa, and lower too than other estimates obtained from the fold mountains of the Western Cape. Coastal fynbos has low productivity and supports a low prey biomass relative to other biomes in South Africa, and thus the density may be justifiably lower than in other more productive habitat types. Of immediate concern is the heavily skewed sex ratio (6M:1F) and low total population size which — together with a permeable boundary fence and known persecution of leopards on neighbouring farms — makes this population vulnerable to both stochastic events and edge effects. Lethal management of leopards that threaten penguins would not be sustainable and thus it is important that a non-lethal barrier has been implemented as it offers the prospect of coexistence between two endangered and charismatic species.